Características do processo orçamentário nas cooperativas de crédito do estado de Minas Gerais - Claudio Duarte Sarkis (2013)
The management literature highlights the importance of the corporate budget in dynamic scenarios like the present, ensuring that organizational planning should involve setting goals, budgeting to meet them and the exercise of managerial control to ensure effective achievement of these goals. While nonprofit and carriers of special features, in the Brazilian financial market, stand out credit unions, which are developing rapidly and strongly demand the adoption of a qualified professional management and implementation of management tools, such as the budget. Based on the characteristics of an effective budgeting process, recommended by the literature, aimed to identify the characteristics of the budget process in credit unions of Minas Gerais, through a descriptive and qualitative search. Based on a sample of 11.5% of the population of credit unions of Minas Gerais, it was found that the surveyed cooperatives do not use the corporate budget in the manner specified in the reference management literature, performing a precarious budget process, or more precisely, a process of projections, which certainly does not generate the results and benefits to be expected that a management tool.